2020
DOI: 10.1002/eco.2244
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting CO2 and water vapour fluxes in dry forest and pasture sites of central Argentina

Abstract: The dry forests of South America are a key player of the global carbon cycle and the regional water cycle, but they are being intensively deforested. We used eddy covariance measurements to compare the temporal patterns of CO 2 and water vapour fluxes and their relationships with environmental variables in dry forest and pastures sites of central Argentina. Ecosystem fluxes showed clear contrasts in magnitude, timing and response to environmental controls between ecosystems. The dry forest displayed higher dai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 95 publications
0
4
0
1
Order By: Relevance
“…These activities, promoted by the establishment of the European civilizations during the past four centuries, have strongly transformed the ecosystem structure (Adámoli et al, 1990; Karlin et al, 2013). Recent studies showed that Dry Chaco woodlands provide key ecosystem services such (1) carbon sequestration (Bonino, 2006; García et al, 2017; Guzmán et al, 2021; Nosetto et al, 2020), (2) temperature regulation (García et al, 2017; Houspanossian et al, 2013; Nosetto et al, 2020), and (3) biodiversity conservation (Coria et al, 2015, 2017; Weiler et al, 2020).…”
Section: Dry Chaco Rangelands Production Systemsmentioning
confidence: 99%
“…These activities, promoted by the establishment of the European civilizations during the past four centuries, have strongly transformed the ecosystem structure (Adámoli et al, 1990; Karlin et al, 2013). Recent studies showed that Dry Chaco woodlands provide key ecosystem services such (1) carbon sequestration (Bonino, 2006; García et al, 2017; Guzmán et al, 2021; Nosetto et al, 2020), (2) temperature regulation (García et al, 2017; Houspanossian et al, 2013; Nosetto et al, 2020), and (3) biodiversity conservation (Coria et al, 2015, 2017; Weiler et al, 2020).…”
Section: Dry Chaco Rangelands Production Systemsmentioning
confidence: 99%
“…Las áreas con vegetación más densa fueron identificadas como prioridad alta, lo cual resultaría razonable y adecuado invertir mayores recursos logísticos para las actividades de restauración en este tipo de ecosistemas, debido a que los bosques proporcionan mayor biomasa y capacidad de enfriamiento de la temperatura superficial y captura de CO 2 (Houspanossian et al, 2013;Nosetto et al, 2020). Si bien en este análisis de identificación de APR no se incorporó la opinión de expertos, la cual tiene un valor importante en este tipo de trabajos (Esmail & Geneletti, 2018;Lopes et al, 2020), los resultados mostraron una asignación lógica y coherente de las áreas prioritarias.…”
Section: Propuesta De áReas Prioritarias Para Restauraciónunclassified
“…The transformation of rangelands into dense shrublands reduced forage supply and domestic livestock accessibility (Kunst et al 2012). Although shrubs compete with grasses for resources, mainly water and light, and impede animal movement (Kunst et al 2003;Blanco et al 2005), they are fundamental in regulating systems, such as water and carbon cycles (Huxman et al 2005;Magliano 2016;Nosetto et al 2020), spatial heterogeneity (Villagra 2000), soil nutrient supply (Anriquez et al 2005;Pérez Harguindeguy et al 2022), and habitat preservation for fauna (Szymañski et al 2021). A significant proportion of shrub species contribute to forage (Allegretti et al 2012;Egea et al 2014); so, strategies seeking to maximise livestock production through shrub removal can conflict with those promoting conservation of native vegetation and provision of other ecosystem services.…”
Section: Introductionmentioning
confidence: 99%